Using magnet to increase retention and stability of lower overdenture: Penggunaan magnet untuk meningkatkan retensi dan stabilitas overdenture rahang bawah - Andi Tenri Biba M. (Makassar Dental Journal, 2020)
Background: Dentures often experience various problems,such as retention and stability.So that thedenture is not looseand stable, it is necessary to add a component, for example the addition of magnets. Overdenture is complete or partial denture supported by a tooth root that has been root canal-treated. The magnet is mounted on the anatomical surface of the base of the denture. While at the root of the tooth, it is prepared for the place of keeper as the magnet attachment. Objective: In this case study, the use of magnets to improve retention and stability in the mandibular complete denture was examined. Case: A 51- year-old woman came to the Prosthodontics Department with complaintsand impaired mastication and function due to loss of all maxillary teeth and leaving two canines in the lower jaw. Patients wanted to have dentures better than before. Management: overdenture is made with magnetic attachment. Conclusion: New mandibular overdenture using magnets has better retention and stability.